Educators’ perceptions of operational competencies required in public schools - Chalmers, Janet (Vaal University of Technology, 2012)
An educator is more than a person who just transmits knowledge. An educator plays many different roles in the lives of learners, colleagues and their immediate community. Educators have the opportunity to influence the community, develop learners holistically, create lifelong learners and reflective thinkers. For an educator to demonstrate such competence across a range of teaching roles and contexts, a vast range of operational competencies are required. The purpose of this study was to examine secondary school educators‟ perceptions of the operational competencies required to function in public schools. The literature study explored the roles of the educator and the operational competencies needed to function in a secondary school. A quantitative survey in the form of a questionnaire was used in the study to analyse the level of agreement that educators attached to certain operational competencies. The level of agreement indicated by the educators is likely to indicate the level of importance that they attach to the operational competency. A probability sampling technique in the form of simple random sampling was used in this study. Random samples were drawn from educators in secondary public schools in the Fezile Dabi and Sedibeng districts. A sample size of 280 educators was used. Of the 280 questionnaires that were administered, 49 were not returned and 20 were incomplete, resulting in 211 usable questionnaires. The results of the survey indicated that the competency factors that educators perceived to be of importance were: communication and behaviour management, interpersonal relationships, planning and assessment, leadership skills and perseverance and organisational commitment. The level of correlation of these identified factors with teaching satisfaction was also assessed- indicating that interpersonal relationships had the highest correlation with teaching satisfaction and factors like planning and assessment, organisational commitment and communication and behaviour management had a moderate influence on teaching satisfaction. Leadership skills and perseverance do not have a great influence on teaching satisfaction. The value of the research is that it makes a useful contribution for planners in the Department of Education of South Africa by making them aware of the operational competencies required by educators in public schools. The results of the research could be used to develop the operational competencies that are not perceived by educators to be of importance and to enhance the teaching satisfaction of educators.
M. Tech. (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Educators perception; Operational competencies; Public schools; Education South Africa; Dissertations, Academic -- South Africa.; Education, Secondary.; Public schools -- Education.; Leadership -- Study and teaching (Secondary)